The impact of direct-acting antiviral treatment on lipid metabolism and insulin resistance in chronic hepatitis C patients: temporary? permanent? - Özdoğan, Osman; Yaraş, Serkan; Ateş, Fehmi; Üçbilek, Enver; Sezgin, Orhan; Altıntaş, Engin (Turkish Journal of Gastroenterology, 2020)
Background/Aims: In previous studies that investigated the impact of direct-acting antiviral (DAA) treatment on lipid metabolism and insulin resistance in chronic hepatitis C patients have been compared to baseline values with either end of treatment or post-treatment values. The results are inconsistent. We evaluated patients throughout the treatment and after treatment. Materials and Methods: 121 patients were included in the study. 93 patients were treated with sofosbuvir/ledipasvir±Ribavirin (RBV), and 28 patients were treated with ombitasvir/paritaprevir/ritonavir+dasabuvir±RBV. Total cholesterol (TC), low-density lipoprotein (LDL), triglycerides (TG) and homeostatic model assessment-insulin resistance (HOMA-IR) levels were measured at the onset of treatment, after the1st month of treatment, at the end of treatment, and 6 and 12 months after the end of treatment. Results: 117 patients were genotype 1. Sustained virological response was 98.4%. HOMA-IR values during treatment were significantly higher than at the beginning of treatment (p=0.0001). At 12 months there was a decrease in HOMA-IR, but this was not statistically significant (p=0.2048). TC and LDL levels were significantly increased in the first month of treatment (TC; 159±30, 180±34 mg/dl; LDL; 84±28, 100±30 mg/dl, respectively) (p<0.0001) and this increase was present during and after treatment. There was no statistically significant increase in TG (p=0120). Both treatment regimens showed similar effects on HOMA-IR, TC, and LDL. Conclusion: Patients with HCV treated with DAAs drugs showed increased IR, TC, and LDL cholesterol levels during treatment. After the end of treatment, IR goes back to normal, while the elevated TC and LDL levels persist indefinitely.